Study effect some plant Extract on Infection with parasite Cryptosporidium parvum in white rat and compere with drug Metronedazole. - Sura Razaq Alobady; Najim Abd alwahad Al-Jadoa (Al-Qadisiyah Journal of Pure Science, 2018)
This study  aimed    to  test  the  effectiveness  of aqueous extracts of garlic bulbs. Alluium  sativum L. and peel  pomegranate Punica  granantum L in treatment  parasite spores  Cryptosporidum  parvum and compared  with  the treatment  of Metronidazole    (Flagyl)   in   laboratory rats.                                                                                                      Conducted on plant extracts hot of garlic and pomagranite the chemical tests  have shown    the presence of active substances  of  both alkaloids, carbohydrates, Flavonides , Alglycosidat, Alsaponyat, Alresins, phenolies.         The result is the appointment of the lethal dose of   moderation   LD50 of aqueous extracts of the garlic, peel the pomegranate after giving the rats doses graded   by the mouth and the results indicate that the dose 7.500 mg / kg of body weight is the lethal dose of aqueous extracts of garlic bulbs and dose limits of 5.750 mg / kg is the lethal dose  to  peel pomegranate.                                                                                 Collects  stool samples from children in the women's and childrenâ€²s hospital.  also collects  all those from infected calves , where he conducts testing samples dye Zail Nelson then isolated and scrubbed   bags    manner   floation    solution    Shidhir diabetes   and    gived  rat (2 x103) bag eggs per rat tube dosage oral and recorded   for the period before dowry of (3-5) days as recorded wounding 100% then  tretment   using aqueous extract to plant garlic. Allium  satvuim   L. peel and pomegranate Punica  granantum L  and drug Metronidazole (Flagyl) concentration of 250, 500, 750 mg / kg, the results shows the effectiveness of the current study, the aqueous extracts in the treatment of the parasites it turns out that the time required to kill the parasite suit inversely with the increasing concentration of extracts also show the efficiency of the aqueous extract of garlic bulbs and metronidazole concentration of 750 mg / kg in the treatment of 100%   after  13   days   of   treatment    with  stops   put  bags  of egg   either  concentration of 500 mg / kg of aqueous extracts  of garlic bulbs  and metronidazole    has  shown  the  efficiency  of treatment    by 100 %  after 15  days  of treatment showed, while the aqueous extract of pomegranate peel concentration 750 mg/kg therapeutic efficiency of 98.41% after 15 days of treatment, while the control group continued to launch until after the egg sacks (15) of treatment.